Characterization of multicopper oxidase-related protein and multicopper oxidase-1 in insects - Peng, Zeyu (Kansas State University, 2014)
Typical multicopper oxidases (MCOs) have ten conserved histidines and one conserved cysteine that coordinate four copper atoms, which are required for oxidase activity. During our studies of insect MCOs, we discovered a gene that we named multicopper oxidase-related protein (MCORP). MCORPs share sequence identity with MCOs, but lack many of the copper-coordinating residues. We identified MCORP orthologs in many insect species, but not in other invertebrates or vertebrates. We purified recombinant Tribolium castaneum (red flour beetle) MCORP. As expected, no oxidase activity was detected. We analyzed expression profiles of TcMCORP and Anopheles gambiae (African malaria mosquito) MCORP. They are constitutively expressed at a low level in many tissues, including ovaries. TcMCORP larval RNAi led to 100% mortality before adult stage. These deaths occurred during the larval to pupal and pupal to adult molts. Pharate pupal RNAi resulted in 20% mortality during the pupal to adult molt, and 100% mortality by one month after adult eclosion. In addition, knockdown of TcMCORP in females prevented oocyte maturation, thus greatly decreasing the number of eggs laid. These results indicate that TcMCORP is an essential gene and that its function is required for reproduction. An understanding of the role MCORP plays in insect physiology may help to develop new strategies for controlling insect pests. A multicopper oxidase-1 (MCO1) ortholog has been identified in all insect species examined so far; thus, MCO1 probably has a conserved physiological function in insects. Most of the well-studied MCOs are laccases, ferroxidases, or ascorbate oxidases. Previously we found Drosophila melanogaster MCO1 has ferroxidase activity and we identified three putative iron binding residues in DmMCO1. Our kinetic analysis of recombinant MCO1 from Drosophila melanogaster, Anopheles gambiae, Tribolium castaneum and Manduca sexta showed that MCO1 orthologs are much better at oxidizing ascorbate than laccase substrates or ferrous iron, suggesting that MCO1 orthologs function as ascorbate oxidases. The putative iron binding residues are required for ascorbate oxidase activity but not ferroxidase and laccase activities. Ascorbate oxidases have been identified only in plants. This is the first identification of ascorbate oxidase in insects. Further studies are needed to understand their physiological function in insects.
Keywords: Multicopper Oxidase-related Protein; Copper; Viability; Reproduction; Multicopper Oxidase 1; Ascorbate Oxidase; Biochemistry (0487)